2023
DOI: 10.1590/1983-21252023v36n104rc
|View full text |Cite
|
Sign up to set email alerts
|

Exchange of germoplasm and genetic diversity to enrichment the Desmanthus genebank

Abstract: The genus Desmanthus presents wide ecogeographical distribution and complex taxonomy. Desmanthus pernambucanus (L.) Thellung, popularly known in Brazil as Jureminha, is a leguminous species native to the Northeast region of Brazil, which stands out by its high protein content, resistance to droughts, and by presenting no toxicity to animals. The objective of this work was to evaluate the genetic diversity of 15 progenies from the Commonwealth Scientific and Industrial Research Organization (CSIRO; Australia), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…It is noteworthy that after the monograph of Desmanthus reported by Luckow (1993), it became evident that most of the germplasm previously identified as D. virgatus was, in fact, D. pernambucanus (L.) Thell (Cook & Schultze-Kraft, 2015). Silva et al (2023) working with Desmanthus observed values close to those found in the present study (Table 4), where the Shannon Index also corresponded to 0.42. A moderate (0.361) Shannon Index value was observed in studies of diversity of accessions of Desmanthus pernambucanus, carried out by Costa et al (2017).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It is noteworthy that after the monograph of Desmanthus reported by Luckow (1993), it became evident that most of the germplasm previously identified as D. virgatus was, in fact, D. pernambucanus (L.) Thell (Cook & Schultze-Kraft, 2015). Silva et al (2023) working with Desmanthus observed values close to those found in the present study (Table 4), where the Shannon Index also corresponded to 0.42. A moderate (0.361) Shannon Index value was observed in studies of diversity of accessions of Desmanthus pernambucanus, carried out by Costa et al (2017).…”
Section: Discussionsupporting
confidence: 84%
“…Pengelly & Liu (2001), evaluating 284 accessions of Desmanthus spp., equivalent to 11 species, from analyzes with Random Amplified Polymorphic DNA (RAPD), observed that there was a higher polymorphism in D. virgatus, D. leptophyllus, and D. pernambucanus, concerning D. pubescens. Silva et al (2023) too observed higher polymorphism, selected primers amplified 38 fragments, with 71.05% polymorphism. The highest polymorphism percentage was shown by ISSR13 (100%), and the lowest by ISSR12 which presented only monomorphic fragments (0% polymorphism).…”
Section: Discussionmentioning
confidence: 91%